Identity Crisis and the Search for the Meaning of Life in Orphaned Children : Narrative Qualitative Study - Nuraly Nuraly; Felisya Cahyani; Eko Sujadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Orphaned adolescents often face various psychological challenges, especially those related to identity crisis and the search for the meaning of life. This study aims to analyze the dynamics of identity crisis and the search for the meaning of life in adolescent orphans. The approach used is qualitative narrative, with three adolescent orphans in Jambi Province as informants. We collected data through in-depth interviews conducted in several meetings. The data obtained were analyzed using the thematic analysis method. The results indicated that the adolescent orphans did not experience a significant identity crisis but were able to show stability in understanding themselves and their roles in the social environment. Despite the loss of their parents being a deep emotional experience, the informants in this study were still able to build a positive self-image and maintain confidence in living their daily lives. In addition, they also showed positive activities in finding the meaning of life, such as setting personal goals, maintaining meaningful social relationships, and developing a spirit to make their remaining family proud. The practical implications of this study can be a reference for Guidance and Counselling (BK) teachers in developing special family guidance and counselling programs that are more responsive to the psychosocial needs of orphaned students in the school environment.